Necessidades de saúde de gestantes de alto risco - Marski, Bruna de Souza Lima (Universidade Federal de São Carlos, 2021)
Pregnancy is a common event in the life cycle of many women and its evolution happens most of the time without adversity. However, a portion of the pregnant women may be more likely to have an unfavorable evolution for their health and / or have a fetus, constituting the group called high-risk pregnancy. Despite the indications and the improvement in the increase in maternal death in recent years, Brazil still presents expressive numbers. Its causes can be the result of complications that occur during pregnancy or after pregnancy and childbirth, and most complications that occur during pregnancy are preventable and treatable. As a strategy to reduce maternal mortality, there is a recommendation for return, more return and assertiveness, with welcoming and individualized actions according to the needs of each pregnant woman. The present study aims to discuss, in the light of the Health Needs Taxonomy proposed by Matsumoto and Cecílio, the needs of women who were pregnant at high risk and the proportion of recommendations for the reception of these women and their needs. It constituted a study with a qualitative approach, carried out from March 2018 to March 2020, in a city in the interior of São Paulo. Documentary research was the selected methodological strategy and for the understanding of the data obtained, we opted for content analysis in the thematic modality proposed by Bardin. Documents analyzed were the transcription of biweekly home visits to 17 high-risk pregnant women carried out during the prenatal period and field notes by visiting nurses. It was possible to establish a translating discussion of the health needs of high-risk pregnant women from three thematic units, as well as to make professional recommendations: ‘HIGH RISK MANAGEMENT: PREPARING THE CONDITION’; ‘INFORMATIONAL NEED TO FOLLOW WITH PREGNANCY’; ‘SOCIAL SUPPORT NETWORK: THE NEED FOR ITS STRENGTHENING AND CONSIDERATION’. They reflect incipient health care for high-risk pregnant women, with clinical practice reduced to a biological dimension. Emerging needs emerge to embrace the emotional demand for the elaboration of pregnancy and the diagnosis of high risk; needs for informational reception to achieve good health conditions; needs to recognize their socio-historical and family context, and needs for professional interventions and management of the different care technologies. The context unveiled by the study allows the review of clinical practices and signals recommendations to professionals for care displaced from the reduced clinic based on dialogic bets.
Health needs of high-rise pregnant women
Keywords: Gravidez de Alto Risco; Cuidado Pré-Natal; Visita Domiciliar; Enfermagem; Pesquisa Qualitativa; Pregnancy; High-risk; Prenatal care; House calls; Nursing; Qualitative research; CIENCIAS DA SAUDE::ENFERMAGEM::ENFERMAGEM OBSTETRICA